Bordetella biofilms: a lifestyle leading to persistent infections - Cattelan, Natalia (2015)
Bordetella bronchiseptica and B. pertussis are Gram-negative bacteria that cause respiratory diseases in animals and humans. The current incidence of whooping cough or pertussis caused by B. pertussis has reached levels not observed since the 1950s. Although pertussis is traditionally known as an acute childhood disease, it has recently resurged in vaccinated adolescents and adults. These individuals often become silent carriers, facilitating bacterial circulation and transmission. Similarly, vaccinated and non-vaccinated animals continue to be carriers of B. bronchiseptica and shed bacteria resulting in disease outbreaks. The persistence mechanisms of these bacteria remain poorly characterized. It has been proposed that adoption of a biofilm lifestyle allows persistent colonization of the mammalian respiratory tract. The history of Bordetella biofilm research is only a decade long and there is no single review article that has exclusively focused on this area. We systematically discuss the role of Bordetella factors in biofilm development in vitro and in the mouse respiratory tract. We further outline the implications of biofilms to bacterial persistence and transmission in humans and for the design of new acellular pertussis vaccines.